The Role of Career Women in Building Children’s Education within Households in Ternate City - Amin, Rifadlin; Sarmin, Nurhadia; Bian, Dewi Ratna; Hamid, Nurul Fathinah F.; Ismail, Nurasma Ila; Agus (Research Horizon, 2025)
This study is motivated by the growing presence of career women in Ternate City who continue to play a central role in fostering children’s education at home. It aims to examine how time management strategies, communication patterns, and supporting and inhibiting factors influence the effectiveness of career women’s educational roles within the family. Employing a qualitative approach, data were collected through in-depth interviews and direct observations. The findings reveal that career women implement time management based on planning, organizing, directing, and controlling to balance work responsibilities and children’s education. Strategies include waking up early, distributing domestic tasks, accompanying children during evening learning activities, and utilizing supplementary tutoring. Communication patterns emphasizing open dialogue, supported by technology, help maintain emotional closeness and monitor children’s learning despite limited maternal time. Key supporting factors include the involvement of husbands, extended families, professional communities, and technological resources, while dual-role burdens, psychological pressures, and gender-based stigma act as significant barriers affecting children’s educational quality. The study emphasizes the need to strengthen family support systems, promote equitable domestic workload distribution, and enhance social awareness to reduce gender stereotypes.